The Importance of Experimental-Traсeologic Research for Studying of Ancient Osseous Products - Skakun, Natalia (Archīum Ateneo, 2017)
Osseous raw materials were widely used in the economic life of diff erent historical epochs in order to make various tools; ornaments; household and military items. Experimental-traceological studies are of great importance for the study of these materials. As a result of many years activity of specialized expeditions organized by the Leningrad Branch of Institute of Archaeology of the USSR Academy of Sciences / Institute for the History of Material Culture of the Russian Academy of Sciences it has been developed a methodology for the integrated study of items from the antler; horn and bone; which included analysis of the features of the preliminary treatment of osseous raw materials; the technology of processing and using various tools and other products; the identifi cation of signs of their utilization; and the characteristics of the main types of stone and metal bone processing tools. The continuation of these studies; undertaken in connection with the accumulation of new sources; allows us to detail the features of the ancient osseous processing industry